Karakteristik Vegetasi pada Areal Berhutan di Sekitar Hak Guna Usaha Perkebunan Kelapa Sawit: Vegetation Characteristics in Forest Areas Surrounding Palm Oil Plantation Concession Area - Setiarno, Setiarno; Junaedi, Ajun; Hartati, Bunga Resa; S, Muhammad Luthfi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
This study was aimed to analyze and describe the characteristics of vegetation in forested areas in and around the Cultivation Rights area of oil palm plantations (PT. GAP and PT. CWJU). Vegetation data was collected using a quadratic plot technique, where the plot itself was assigned using purposive systematic sampling. Vegetation data in the research plots were analyzed using Microsoft Excel by involving index calculations, namely the Important Value Index/INP or Important Species Value/NPJ, species dominance index, diversity index, richness index, evenness index, and species similarity index. The results of the study in the observation plots have recorded 43 species of woody plants that can be grouped into 34 genera and 21 families. Eugenia uniflora and Shorea macrantha at the research site are more dominant in all growth phases. It is indicated that there is no concentration of dominance by a species in the research plot (C = 0.10 – 0.14), the H’ value is classified as moderate/moderate stability (1 < H’ < 3.22) which reflects sufficient species diversity and relative abundance, the richness index ranges from 1.90 – 2.32 which is generally low (R < 3.5), the evenness index ranges from fairly even to almost even (E = 0.62 – 0.94), and the species similarity index of 0.61 is classified as moderate. Keywords: vegetation, plant species, plant community